Strength endurance and fatigability: candidate risk factors for hamstring re-injury in sprint sports? - Polspoel, K.; Vanrenterghem, J.; Bogaerts, S. (British Journal of Sports Medicine, 2021)
Background Hamstring strain injuries (HSI) are characterized by a very high recurrence rate. Despite indications from the field that deficits in strength endurance and fatigability play a role in (re-)injury, screening for these in Return To Sport (RTS) decision making is still not common and requires further investigation.